Topical Application of Povidone Iodine to Minimize Post Appendectomy Wound Infection - Mamoon Othman Khalid Alabdulla; Asaad Mohammed Kadhim; Hussein Abduljabbar Shihab Al-Katrani (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Despite the use of prophylactic antibiotic and sterilization techniques and nemours methodsof wound care, post appendectomy wound infection is still high.Methods: Arandomized controlstudy (RCS) has been implied to prove, whether uses of povidone iodinejust prior to wound suturing could decrease surgical wound infection rates after surgery for appendectomy.Atotal number of 120 patients operated for cute appendicitis with open appendectomy at AL-MawaniTeachingHospital during the period from march 2016 to October 2020.Results: After appendectomy patients was randomize into three groups, group A which include 40 patientsthe subcutaneous tissue was irrigated with 1% diluted povidone-iodine solution before skin closure.Group B which contained other 40 patients the wound has been washed with normal saline, and in groupC(controlgroup) no irrigation was done.All patients were followed for surgical site infection according toSouthampton wound grade system for ten days after surgery.In this study we notice that areductionhappenedin the number of wound infection in group Acompare with group B and C.Conclusion: The uses of povidone iodine 1% before skin closure is an effective method in reducing the rateof infection of the wound after surgery for acute appendicitis.